The language machine: psycholinguistics in review. - Altmann, Gerry T. M. (British Journal of Psychology, 2001)
Psycholinguistics is the empirical and theoretical study of the mental faculty that underpins our consummate linguistic agility. This review takes a broad look at how the field has developed, from the turn of the 20th century through to the turn of the 21st. Since the linguistic revolution of the mid-1960s, the field has broadened to encompass a wide range of topics and disciplines. A selection of these is reviewed here, starting with a brief overview of the origins of psycholinguistics. More detailed sections describe the language abilities of newborn infants; infants' later abilities as they acquire their first words and develop their first grammatical skills; the representation and access of words (both spoken and written) in the mental lexicon; the representations and processes implicated in sentence processing and discourse comprehension; and finally, the manner in which, as we speak, we produce words and sentences. Psycholinguistics is as much about the study of the human mind itself as it is about the study of that mind's ability to communicate and comprehend. Reprinted by permission of the publisher.